Aged layered double hydroxide nanosheet–polyvinyl alcohol dispersions for enhanced gas barrier coating performance. Issue 10 (6th September 2021) - Yu, Jingfang; Chen, Chunping; Gilchrist, James B.; Buffet, Jean-Charles; Wu, Zhonghua; Mo, Guang; Xie, Fei; O'Hare, Dermot
Abstract : The oxygen transmission rate of a PET coated film showed a 37-fold decrease using a dispersion of LDH nanosheets in polyvinyl alcohol that was prior aged for 8 weeks compared to the film coated with the equivalent freshly prepared LDH/PVA dispersion. Abstract : Whilst applying a coating layer to a polymer film is a routine approach to enhance the gas barrier properties of the film, it is counter-intuitive to consider that the gas barrier performance of the film would improve by ageing the coating dispersion for weeks before application. Herein, we report that the oxygen barrier performance of a 12 μm PET film coated with a dispersion of inorganic nanosheets in polyvinyl alcohol can be significantly enhanced by ageing this coating dispersion for up to 8 weeks before application. We found up to a 37-fold decrease in the oxygen transmission rate (OTR) of the PET coated film using aged dispersions of [Mg0.66 Al0.33 (OH)2 ](NO3 )0.33 layered double hydroxide nanosheets (Mg2 Al-LDH NS) in polyvinyl alcohol (PVA) compared to the film coated with an equivalent freshly prepared LDH/PVA dispersion. A limiting OTR value of 0.31 cc m −2 day −1 was achieved using the PET film coated with a 3 week aged LDH NS/PVA dispersion. X-ray diffraction experiments show that the degree of in plane alignment of LDH NS on the PET film surface increased significantly from 70.6 ± 0.6 to 86.7 ± 0.6 (%) (100% represents complete alignment of LDH NS platelets on the film surface) for the 4 week aged dispersion compared to the freshly prepared layer. We postulate that when the Mg2 Al-LDH NS are aged in PVA the coiled PVA aggregates start to unwrap and attach onto the Mg2 Al-LDH NS through hydrogen bonding and eventually form a hydrogen bonded ordered network that facilitates the alignment of nanosheet dispersions during the coating process. Our results suggest that the ageing of inorganic nanosheet dispersions in PVA or other potential hydrogen bonding adhesive systems could be a general approach to improve the alignment of the nanosheets on the polymer film surface once applied and thus improve their performance characteristics for barrier coating applications.